Hegel als Herausforderung: zu W. Kerns Beiträgen in Auseinandersetzung mit G. W. Fr. Hegel - Neufeld, Karl H. (Zeitschrift für katholische Theologie, 2002)
Christian thinking in the modem world is believed opposed to positions contradicting the aims of Gospel und Christian life. One of the outstanding modern leaders was Hegel; with him and his work W. Kern dealed along his academic life to overcome the indicated gap. A fruitful discussion with this philosophy can give even to catholic interpretation of reality new power and the possibility of a more adequated vision and another way of dealing with expressions of humanity of today.